Adaptor protein 2 regulates receptor-mediated endocytosis and cyst formation in Giardia lamblia - Rivero, Maria Romina (2010)
The parasite Giardia lamblia possesses PVs (peripheral vacuoles) that function as both endosomes and lysosomes and are implicated in the adaptation, differentiation and survival of the parasite in different environments. The mechanisms by which Giardia traffics essential proteins to these organelles and regulates their secretion have important implications in the control of parasitedissemination. In the present study, we describe the participation of the heterotetrameric clathrin-adaptor protein gAP2 (Giardia adaptor protein 2) complex in lysosomal protein trafficking.A specific monoclonal antibody against the medium subunit (gu2) of gAP2 showed localization of this complex to the PVs, cytoplasm and plasma membrane in the growing trophozoites. gAP2 also co-localized with clathrin in the PVs, suggesting its involvement in endocytosis. Uptake experiments using standard molecules for the study of endocytosis revealed that gAP2 specifically participated in the endocytosis of LDL (low-density lipoprotein). Targeted down-regulation of the gene encoding gu2 in growing and encysting trophozoites resulted in a large decrease in the amount of cell growth and cyst wall formation, suggesting a distinct mechanism in which gAP2 is directly involved in both endocytosis and vesicular trafficking.